A CASE OF DERMATITIS IN PIGLETS - ΣΤΟΦΟΡΟΣ Ε.; ΡΑΝΤΣΙΟΣ Α.; ΜΑΣΤΡΟΓΙΑΝΝΗ-ΚΟΡΚΟΛΟΠΟΥΛΟΥ Μ. (Journal of the Hellenic Veterinary Medical Society, 1974)
The authors describe a case of dermatitis in piglets. The histological findings (presence of eosinophilinij polynucleatei cells in the skin) and the impossibility of isolating a pathological agent suggest an allergic etiology of this dermatitis.